KEBIJAKAN ASIMILASI NARAPIDANA PADA PANDEMI COVID-19 DALAM PERSPEKTIF HAK ASASI MANUSIA - Januarsa Adi Sudharma Kadek (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
This research aims to find out the process of assimilation policy and the legal basis for making the movement. The policy of asymptomatic persons in the COVD-19 pandemic made by the government with the legality of PERMENKUMHAM No. 32 of 2020 caused polemics. Assimilation is a right owned by prisoners, on the other hand the assimilation program makes the community worry about an increase in crime. This research method uses normative research that refers to legal materials by studying theories, concepts and laws and regulations related to this research. The technique of collecting legal materials is by studying literature. Based on this research, it can be concluded that the basis of the policy of assimilation of prisoners during the COVD-19 pandemic is the occurrence of emergencies with the presence of COVID-19 which is an infectious disease from manusa to manusa and correctional institutions in Indonesa with over capacity conditions, so the government through the minister of law and human rights made a policy on the assimilation of prisoners.With the creation of the assimilation policy is the right step in the midst of force majure conditions and it is the government's commitment in prioritizing the safety of